2017
DOI: 10.1021/acs.iecr.7b00113
|View full text |Cite
|
Sign up to set email alerts
|

A Generalizable Multigram Synthesis and Mechanistic Investigation of YMnO3 Nanoplates

Abstract: The reproducible gram-scale synthesis of crystalline nanoscale multiferroics is critical for the development of the next generation of commercially relevant electronic devices. Of the subset of multiferroic materials, yttrium manganese oxide (YMnO3) is highly attractive, because of its large magneto-electric coupling constants and the recent observation of giant polarization under pressure in these types of rare earth manganites. Utilizing a unique synthetic methodology that combines metal–oleate thermal degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
(118 reference statements)
2
4
0
Order By: Relevance
“…We analyzed the chemical composition for h-YMnO 3 using XPS. The full-spectrum scan (Figure 4A) revealed the presence of the chemical elements Y, Mn, O, and C, whose binding energies agree with those reported in the literature [17,20]. The peak associated with C is due to the carbon-based tape used to fix the sample while analyzed.…”
Section: Characterizationsupporting
confidence: 84%
See 2 more Smart Citations
“…We analyzed the chemical composition for h-YMnO 3 using XPS. The full-spectrum scan (Figure 4A) revealed the presence of the chemical elements Y, Mn, O, and C, whose binding energies agree with those reported in the literature [17,20]. The peak associated with C is due to the carbon-based tape used to fix the sample while analyzed.…”
Section: Characterizationsupporting
confidence: 84%
“…Additionally, semi-triangular structures attached to the surface of the microrods appear after calcination. Comparing the morphology obtained in this work with those reported for h-YMnO 3 [17][18][19], we found that those microstructures have not been reported for this oxide. This suggests that the formic acid reaction with the yttrium and manganese nitrates allows this morphology to form, avoiding the surfactants used.…”
Section: Characterizationsupporting
confidence: 49%
See 1 more Smart Citation
“…Few different studies dealing with the preparation of YMnO 3 by molten salt synthesis have been already reported [26][27][28]. In all cases, either NaCl or the eutectic mixture of NaCl and KCl were used as the reaction medium.…”
Section: Introductionmentioning
confidence: 99%
“…Another theme that emerges from this collection is advances in materials for energy applications. ,, These articles discuss solar cells, supercapacitors, and hydrogen storage. This Virtual Special Issue also features new work on CO 2 capture and storage, carbon nanotube assemblies, gas separation, and synthesis of nanomaterials for electronic devices …”
mentioning
confidence: 99%